2020
DOI: 10.23917/jisel.v3i1.10191
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Preference of Customers Towards Islamic Banking: Evidence from Malaysia

Abstract: The purpose of this research is to investigate the pivotal determinants influencing the consumer’s preference towards the products and services of Islamic banking, apart from reviewing previous studies that considered perceived religiosity has an intense relationship with the individual’s intention and attitude. Moreover, this study also examines the direct relationship between the preference of customers and the Service quality offered by Islamic banks. This study utilized quantitative approach through conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
3
5
0
1
Order By: Relevance
“…The results of multiple regression to identify the effect of Attitudes, Subjective Based on the probability and coefficient value, hypothesis 1 which reads attitudes have a positive effect on intentions to patronize Islamic banking is accepted. The results of this study support of previous studies which stated that attitude have a positive effect on intention to patronize Islamic banks (Allah Alqasa et al, 2014;Amin, 2017;Ayyub et al, 2019;Bananuka et al, 2019;Dawami, 2020;Dzuljastri Abdul & Abduh, 2012;Echchabi & Aziz, 2012;Ganesan et al, 2020;Kaawaase & Nalukwago, 2017;Rahman, 2014;Reni & Ahmad, 2016;Sulaiman et al, 2016) Alqasa et al, 2014;Amin, 2017;Aziz et al, 2018;Bananuka et al, 2019;Dzuljastri Abdul & Abduh, 2012;Echchabi & Aziz, 2012;Ganesan et al, 2020;Halid et al, 2019;Lajuni et al, 2017;Najakh et al, 2018;Rahman, 2014;Reni & Ahmad, 2016). However, this research in line with previous studies which stated that subjective norms have no effect on intention (Ali et al, 2015;Ayyub et al, 2019;Charag et al, 2019;Sulaiman et al, 2016).…”
Section: Regression Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of multiple regression to identify the effect of Attitudes, Subjective Based on the probability and coefficient value, hypothesis 1 which reads attitudes have a positive effect on intentions to patronize Islamic banking is accepted. The results of this study support of previous studies which stated that attitude have a positive effect on intention to patronize Islamic banks (Allah Alqasa et al, 2014;Amin, 2017;Ayyub et al, 2019;Bananuka et al, 2019;Dawami, 2020;Dzuljastri Abdul & Abduh, 2012;Echchabi & Aziz, 2012;Ganesan et al, 2020;Kaawaase & Nalukwago, 2017;Rahman, 2014;Reni & Ahmad, 2016;Sulaiman et al, 2016) Alqasa et al, 2014;Amin, 2017;Aziz et al, 2018;Bananuka et al, 2019;Dzuljastri Abdul & Abduh, 2012;Echchabi & Aziz, 2012;Ganesan et al, 2020;Halid et al, 2019;Lajuni et al, 2017;Najakh et al, 2018;Rahman, 2014;Reni & Ahmad, 2016). However, this research in line with previous studies which stated that subjective norms have no effect on intention (Ali et al, 2015;Ayyub et al, 2019;Charag et al, 2019;Sulaiman et al, 2016).…”
Section: Regression Resultssupporting
confidence: 90%
“…This explains that the higher the positive response or positive attitude of a person to use Islamic banks, the stronger intention to transact with Islamic banks. Several previous studies found a significant relationship between attitudes towards intention to use Islamic banks (Ganesan et al, 2020;Dawami, 2020;Ayyub et al, 2019;Bananuka et al, 2019;Kaawaase & Nalukwago, 2017;Amin, 2017;Sulaiman et al, 2016;Reni & Ahmad, 2016;Alqasa et al, 2014;Rahman, 2014;Echchabi & Aziz, 2012;Dzuljastri Abdul & Abduh, 2012). Furthermore, the results of other studies indicate that attitudes have no effect on customer intentions to use Islamic banks (Halid et al, 2019;Najakh et al, 2018;Ali et al, 2015).…”
Section: Attitudementioning
confidence: 93%
“…Nevita & Arifin (2015) have stated that religious factors or perceptions that are only based on religious reasons do not necessarily affect people's behavior towards decisions in using a type of banking service. This also agrees with the research conducted by Dawami (2020), Butt et al (2018), Lajuni et al (2017), Bodibe et al (2016), Ali et al (2015), Pepinsky (2010) and Adawiyah (2010) stated that religion is not the main factor to attract consumers using Islamic banks, but there are other important factors in marketing Islamic banking. And the interesting thing is consumers have done something they liked rather than did something because of the need for obligations.…”
Section: Islamic Banking: Reality and Hopesupporting
confidence: 89%
“…Customers' attitudes have been identified as one of the most important factors influencing Islamic banking business (Dawami, 2020). Customers' behavior and Islamic bank qualities are closely related to banks' competitiveness (Utami et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%